2017
DOI: 10.1016/j.laa.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Hadamard powers of some positive matrices

Abstract: Positivity properties of the Hadamard powers of the matrix 1 + x i x j for distinct positive real numbers x 1 , . . . , x n and the matrix | cos((i − j)π/n)| are studied. In particular, it is shown that (1 + x i x j ) r is not positive semidefinite for any positive real number r < n−2 that is not an integer, and | cos((i − j)π/n)| r is positive semidefinite for every odd integer n ≥ 3 and n − 3 ≤ r < n − 2.2010 Mathematics Subject Classification. 15B48, 15A45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In her 2017 paper [81], Jain provided a remarkable strengthening of the result mentioned at the end of the previous proof, which removes the dependence on t entirely. Theorem 6.2 (Jain [81]). Let…”
Section: Power Functionsmentioning
confidence: 74%
“…In her 2017 paper [81], Jain provided a remarkable strengthening of the result mentioned at the end of the previous proof, which removes the dependence on t entirely. Theorem 6.2 (Jain [81]). Let…”
Section: Power Functionsmentioning
confidence: 74%
“…. , x n are distinct positive real numbers and J n be the matrix of order n with each of its entries equals to 1, then X and J n are both ID, but their sum is not ID (see [12,Theorem 1.1]). The Cauchy matrix C = [c ij ] = 1 i+j , 1 ≤ i, j ≤ 3 is ID (see [1]), but its square C 2 is not ID because det(C 2 )…”
Section: By Theorem 8mentioning
confidence: 99%
“…If r > 0, then we denote the rth Hadamard power of a nonnegative matrix A = [a ij ] by A or (or (A) •r ), where A or = [a r ij ]. A lot of interest has been shown in studying the real entrywise powers preserving the positive semidefiniteness of various families of matrices, see [2,5,7,8,9,10,12,13]. A well-known result is that if A is a nonnegative PSD matrix of order n and r ≥ n − 2, then A •r is PSD.…”
mentioning
confidence: 99%
“…The long history of this field starts with the Schur product theorem (see [5]), followed by the works of Schoenberg [9], Rudin [8] and others. In particular, the study of entrywise power functions x → x α has been of special interest to several mathematicians (see [1,2,3,4,6]). By the Schur product theorem, the mth Hadamard power A •m := [a m ij ] of any p.s.d.…”
Section: Introductionmentioning
confidence: 99%
“…They considered the matrix A ∈ P + n with (i, j)th entry 1 + ij and showed that if α is not an integer and 0 < α < n − 2, then A •α is not positive semi-definite for a sufficiently small positive number . Later, Jain [6] showed that this remains true if ij is replaced with x i x j for any distinct positive real numbers x 1 , . .…”
Section: Introductionmentioning
confidence: 99%